In situ antibody phage display yields optimal inhibitors of integrin α11/β1 - Eugenio Gallo; Abdellali Kelil; Peter E. Bayliss; Ajitha Jeganathan; Olga Egorova; Lynda Ploder; Jarrett J. Adams; Patricia Giblin; Sachdev S. Sidhu (Taylor & Francis Group, 2020)
Integrins are transmembrane multi-conformation receptors that mediate interactions with the extracellular matrix. In cancer, integrins influence metastasis, proliferation, and survival. Collagen-binding integrin-α11/β1, a marker of aggressive tumors that is involved in stroma-tumor crosstalk, may be an attractive target for anti-cancer therapeutic antibodies. We performed selections with phage-displayed synthetic antibody libraries for binding to either purified integrin-α11/β1 or in situ on live cells. The in-situ strategy yielded many diverse antibodies, and strikingly, most of these antibodies did not recognize purified integrin-α11/β1. Conversely, none of the antibodies selected for binding to purified integrin-α11/β1 were able to efficiently recognize native cell-surface antigen. Most importantly, only the in-situ selection yielded functional antibodies that were able to compete with collagen-I for binding to cell-surface integrin-α11/β1, and thus inhibited cell adhesion. In-depth characterization of a subset of in situ-derived clones as full-length immunoglobulins revealed high affinity cellular binding and inhibitory activities in the single-digit nanomolar range. Moreover, the antibodies showed high selectivity for integrin-α11/β1 with minimal cross-reactivity for close homologs. Taken together, our findings highlight the advantages of in-situ selections for generation of anti-integrin antibodies optimized for recognition and inhibition of native cell-surface proteins, and our work establishes general methods that could be extended to many other membrane proteins.